2018
DOI: 10.3390/ijerph15112549
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Family and Food-Related Life Satisfaction in the Relationships between Family Support, Parent Work-Life Balance and Adolescent Life Satisfaction in Dual-Earner Families

Abstract: This study explored the associations between family support and satisfaction with life, food-related life and family life. It also assessed the associations between both parents’ work-life balance and satisfaction with life, food-related life and family life among adolescent children from dual-earner families. Questionnaires were administered to 303 dual-earner families with one child between 10 and 17 years in Temuco, Chile. Adolescents answered the Satisfaction with Life Scale (SWLS), Satisfaction with Food-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 88 publications
(188 reference statements)
12
45
0
2
Order By: Relevance
“…In fact, family climate has a direct and positive relationship with LS, which confirms a part of the first hypothesis proposed. This result is consistent with previous research highlighting the close link between parent-child relations and psychosocial adjustment [32,38,51]. A socio-family environment in which the members feel close ties of affective cohesion, where adolescents can openly express their opinions, emotions, and behaviours to their parents without being judged, and where there are no major sources of conflict favours youths' self-perception of subjective well-being, happiness, and LS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In fact, family climate has a direct and positive relationship with LS, which confirms a part of the first hypothesis proposed. This result is consistent with previous research highlighting the close link between parent-child relations and psychosocial adjustment [32,38,51]. A socio-family environment in which the members feel close ties of affective cohesion, where adolescents can openly express their opinions, emotions, and behaviours to their parents without being judged, and where there are no major sources of conflict favours youths' self-perception of subjective well-being, happiness, and LS.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies also show that family climate has a strong relationship with adolescents' well-being [29][30][31], behaviour [32,33], social, physical, emotional, and intellectual development, and with the formation of their self-concept [27]. Family climate refers to the psychosocial and institutional family characteristics and its settings [34] and can be conceptualized as the perception and interpretation of the inner world of the family and its relationships [35].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the relative contribution of the family and food domains to overall life satisfaction, Schnettler et al [ 14 ] found that the contribution of satisfaction with family life was slightly higher than that of satisfaction with food-related life in undergraduate students’ life satisfaction in Chile. However, when the contribution of these two domains on mothers’ and adolescents’ life satisfaction was assessed, the family domain was of higher importance than satisfaction in the food domain [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that having good relationships within the family and greater levels of attachment (how close family members are to each other) are beneficial for a family member’s life satisfaction [ 53 ]. In this regard, different studies using the life satisfaction bottom-up approach have supported a positive relationship between satisfaction with family life and overall life satisfaction at an individual level in different countries [ 6 , 8 , 18 , 21 , 41 , 47 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation